Tourist Decisions Visit Attractions In Lampung Province Through Electronic Word Of Mouth (E-WOM) - Novita Sari; Muhammad Saputra (Proceeding International Conference on Information Technology and Business, 2018)
Tourism is a potential source of income. The phenomenon of the increase and decrease of visiting tourists is needed an information media to introduce the tourist attraction of Lampung Province to increase the number of tourists visiting Lampung Province. The purpose of this study was to determine the effect of Electronic Word of Mouth (E-WOM) with the Intensity dimension, Valence of Opinin, Conten on Tourist Decisions Visiting Attractions in Lampung Province. This type of research is this associative study. The sampling used in this study was purposive sampling with as many samples. Methods Analysis of data in this study using path analysis. The results of the analysis There is the influence of Intensity on the decision to visit tourists to Lampung Province. There is no effect of Valence of Opinin on decisions visiting tourists to Lampung Province. There is a Content influence on the decision to visit tourists to Lampung Province. Content variable (X3) affects the most on visiting decisions by 73.2%Keywords: Electronic Word Of Mouth (E-WOM), Visiting Decision, Tourism Object, Lampung